Electrochemical Behavior of Trazodone at Mercury and Glassy Carbon Electrodes and Voltammetric Methods for its Determination - Kacar, C.; Durmus, Z.; Kilic, E. (Asian Journal of Chemistry, 2014)
Electrochemical oxidation and reduction characteristics of trazodone were studied on glassy carbon electrode (GCE) and hanging mercury drop electrode (HMDE), respectively. Diffusion-adsorption behavior and electrochemical parameters such as diffusion coefficient, number of electrons transferred and proton participated to its electrode mechanisms and surface coverage coefficient were calculated using the results of cyclic voltammetry and square-wave voltammetry. Quasi-reversible and adsorption controlled reduction mechanism was proposed on HMDE and oxidation with two-electron/two-proton irreversible oxidation mechanism controlled by adsorption with some diffusion contribution on GCE was proposed. Experimental parameters were optimized to develop new, accurate, rapid, selective and simple voltammetric methods for direct determination of trazodone in pharmaceutical dosage forms and spiked human serum samples without time-consuming steps prior to drug assay. In square-wave cathodic adsorptive stripping voltammetry, limit of detection (LOD) was found as 4.32 nM. Proposed methods were successfully applied to determine the trazodone content of commercial pharmaceutical preparations and spiked human serum. The methods were found to be highly accurate and precise, having a relative standard deviation of less than 5 % for all applications.